Adaptive Control with Approximated Policy Search Approach - Agus Naba (Journal of Engineering and Technological Sciences, 2010)
Most of existing adaptive control  schemes are designed to minimize error  between  plant  state  and  goal  state  despite  the  fact  that  executing  actions that are predicted to result in smaller errors only can mislead  to non-goal states. We develop an adaptive control scheme that involves manipulating a controller of  a  general  type  to  improve  its  performance  as  measured  by  an  evaluation function. The developed method is closely related  to a theory of Reinforcement Learning (RL) but imposes a practical assumption made for faster learning. We assume  that  a  value  function  of  RL  can  be  approximated  by  a  function  of Euclidean distance from a goal state and an action executed at the state. And, we propose  to  use  it  for  the  gradient  search  as  an  evaluation  function.  Simulation results provided through application of the proposed scheme to a pole -balancing problem using a linear  state feedback controller and fuzzy controller verify the scheme's efficacy.